Coping with extremes, creating comfort: User experiences of 'low-energy' homes in Australia. (May 2019) - Sherriff, Graeme; Moore, Trivess; Berry, Stephen; Ambrose, Aimee; Goodchild, Barry; Maye-Banbury, Angela
Abstract: Low- and zero-energy homes are core elements in transitioning the housing stock towards a more environmentally sustainable model that responds to concerns about climate change and the need for energy demand reduction. Whilst there is a growing body of work on the technical performance of these homes, less attention has been paid to the experiences of users, particularly in cooling-dominated climates. Drawing on interviews that utilise an oral history approach with householders in Lochiel Park Green Village in South Australia, this research situates experiences and energy practices within individual housing histories in order to better understand the relationship between the occupant, the building and the resultant energy use. Within the context of debates around adaptive comfort practices this innovative method reveals that, despite the expectations of some residents, moving to a 'low-energy' home has reduced rather than eliminated their active involvement in maintaining a thermally comfortable environment.